The Future of Reading and Academic Libraries - Horava, Tony; Durant, David (Université d'Ottawa | University of Ottawa, 2015)
The e-book is raising fundamental questions around the dynamics and habits of reading; the role of books in the academic library; and the role of librarians in addressing new realities of reading and learning. Print and digital texts foster different styles of reading and different ways of thinking and doing research. This paper examines implications of the shift from print to digital reading and how academic libraries in particular should respond. Academic libraries should treat print and electronic books as complementary, not interchangeable, and commit themselves to maintaining hybrid collections that support the full range of learning and research styles
Keywords: reading; books; academic libraries; collections; hybrid